Creating critical thinkers with the Four Dimensions Model of critical literacy pedagogy - Arvianti, Indah (2025)
Language choices, influenced by mass media editors, political elites, lawmakers, educational designers, and other text producers, can be used to oppress the public. Readers need to be sensitive to the underlying messages in all texts. Critical literacy pedagogy is a tool to reveal injustice and unequal power relations in text, enhancing students’ critical language awareness and empowering them to examine both the word and the world critically. However, many readers remain unaware of the subtle ways language can reinforce critical issues such as inequality and sustain dominant ideologies. This research aims to develop language learning tools using the four dimensions model of critical literacy pedagogy to uncover power, domination, and social systems within texts. This model explores how the Four Dimensions Model disrupting commonplace, considering multiple viewpoints, focusing on socio-political systems, and taking action, which can improve students' critical literacy skills by asking students critically to generate critical thinking. Integrating the Four Dimensions Model improves students’ ability to critically recognize biases and articulate more socially aware interpretations.